Bioprinting and Intellectual Property: Challenges, Opportunities, and the Road Ahead - Antreas Kantaros; Theodore Ganetsos; Florian Ion Tiberiu Petrescu; Elli Alysandratou (Bioengineering)
Bioprinting, an innovative combination of biotechnology and additive manufacturing, has emerged as a transformative technology in healthcare, enabling the fabrication of functional tissues, organs, and patient-specific implants. The implementation of the aforementioned, however, introduces unique intellectual property (IP) challenges that extend beyond conventional biotechnology. The study explores three critical areas of concern: IP protection for bioprinting hardware and bioinks, ownership and ethical management of digital files derived from biological data, and the implications of commercializing bioprinted tissues and organs. Employing a multidisciplinary approach, the paper analyzes existing IP frameworks, highlights their limitations when applied to bioprinting, and examines ethical dilemmas, such as ownership of bioprinted human tissues and the commodification of biological innovations. Findings suggest that current IP laws inadequately address the complexities of bioprinting, particularly in managing the intersection of proprietary technologies and ethical considerations. The study underscores the need for adaptive legal and ethical frameworks to balance innovation with equitable access and sustainability. Recommendations include the development of tailored IP policies for bioprinting and enhanced international collaboration to harmonize legal protections across jurisdictions. This work aims to provide a comprehensive foundation for stakeholders to navigate the rapidly evolving landscape of bioprinting IP.